Kajian Tafsir Huruf Muqaththa’ât Dalam Tafsir Lathâif Al-Isyârât - Rizqi Romdhon, Muhammad; Masruchin, Masruchin (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2023)
This research aims to find out what the muqaththa'āt letters mean in the interpretation of Lathāif al-Isyārāt with a tasawuf and linguistic approach in understanding the muqaththa'āt letters, so that one can understand what meaning is contained in the word which is full of secrets. This research uses a type of qualitative research that is descriptive through library research. Based on the research that has been done, it can be concluded that the muqaththa'āt letters in the Qur'an consist of fourteen letters contained in twenty-nine letters. The meaning of the letters muqaththa'āt in the interpretation of Lathāif al-Isyārāt has the meaning of description of the names and attributes of Allah, the description of the secrets of Allah, the description of the oath, the description of the names and attributes of the Prophet, the mention of the names of the Angels, the description of the attributes, secrets and the recompense of the servants of Allah. As well as personification of character traits, animal metaphors, rebab sound metaphors, mention of supernatural objects, mention of unseen places, depictions of the Last Day and depictions of life and destiny's journey